2007
DOI: 10.1354/vp.44-2-161
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Study of 52 Feline Epulides

Abstract: Abstract. A retrospective study was performed to characterize 52 new cases of feline epulides between 1995 and 2001, with clinical and pathological results classified according to Head's histopathologic criteria for canine epulides. The incidence of the fibromatous, acanthomatous, ossifying, and giant cell epulis were respectively 57.7% (30/52), 7.7% (4/52), 5.8% (3/52), and 28.8% (15/52). Giant cell epulides presented significant differences in clinical behavior compared with the fibromatous type, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 26 publications
3
53
2
Order By: Relevance
“…While the WHO classifications list giant cell epulis as a tumour‐like lesion, a recent study suggested it may in fact be a variant of the fibromatous and ossifying epulis. In that study cats with epulides were between 8 months and 20 years old (de Bruijn and others 2007). The feline inductive odontogenic tumour is a rare neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…While the WHO classifications list giant cell epulis as a tumour‐like lesion, a recent study suggested it may in fact be a variant of the fibromatous and ossifying epulis. In that study cats with epulides were between 8 months and 20 years old (de Bruijn and others 2007). The feline inductive odontogenic tumour is a rare neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 The variable TRAP reactivity among lesions with numerous, moderate, or few MNGCs is interesting, although the significance of this finding is unknown. We cannot rule out 2 different cells of origin for the MNGCs in these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,13,17,18,21,22,25 Although human peripheral giant cell granulomas are generally considered reactive and non-neoplastic, the cause of these lesions is poorly understood. 13,17,18 Six reported cases of canine peripheral giant cell granuloma did not recur after surgical excision.…”
mentioning
confidence: 99%
“…For this reason, it has been included in this classification. 15,16 Finally, the fibromatous form of POF is the most frequently diagnosed odontogenic tumour in cats. 16 The aim of this study was to assess the prevalence of oral diseases in Portuguese cats, over a 6-year period, in order to evaluate the distribution of inflammatory and neoplastic lesions, while simultaneously correlating them with sex, breed and life stage.…”
Section: Introductionmentioning
confidence: 99%